(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
An ideal solar absorber surface coating must have good optical properties like high solar absorptance with minimum solar emittance. Development of new coating is fabricated by embedding metallic particles composed of a nickelaluminium (NiAl) alloy into the black paint as well as solar selective black nickel-cobalt (NiCo) electroplating on aluminium alloys with nickel undercoat is done. Characterization of such solar selective surface coatings are done and compared with commercial black paint. A new and affordable solar selective surface coating having higher solar absorption efficiency with low in-frared emittance compared to the commercial black paint coating used in most ordinary solar water heating systems has been developed. Characterization of coating includes Optical properties studies of coatings, Surface morphology and XRD studies, and solar water heater performance with new coatings.